Risk of cervical intraepithelial neoplasia grade 3 or higher (CIN3+) among women with HPV-test in 1990-1992 - Riibe, Marit Østlyngen (UiT Norges arktiske universitet, 2020)
Background/objective: Long-term follow-up of patients with positive tests for Human Papilloma Viruses (HPV) is rarely studied. The study objective was to compare HPV status at baseline with the outcome of CIN3+ in the follow-up period of 28 years. Materials and methods: All women referred to the HPV outpatient clinic at the University Hospital of Northern Norway (UNN) in 1990-1992, having a HPV test performed during that time, were included in this retrospective cohort. An exposed cohort with positive high-risk (HR) HPV test was compared to a control cohort with negative HR-HPV test. Both cohorts were followed up to the last time-point of observation of 28 years. Results: The risk of CIN2+ among HPV positive and HPV negative women was 57.0% (127/223) and 17.4% (73/419), respectively (p<0.01). Among the 223 HR-HPV positive women, 102 (45.7%) developed CIN3+, while 44 (10.5%) out of 419 HPV negative women developed CIN3+ (p<0.01). The overall cumulative incidence of CIN3+ was 22.7%. Women with HPV33 had the highest incidence of CIN3+, but HPV16 provided the greatest long-term risk of CIN3+. The incidence of CIN3+ was similar for women with a negative HR-HPV test and women with a positive low-risk (LR) HPV test, including HPV 6 and 11. Conclusion and consequences: HPV status at baseline is predictive for women ́s subsequent risk of developing CIN3+. Women with a positive HR-HPV test in 1990-1992 had a significantly higher risk of CIN3+ during 28 years of follow-up compared to HR-HPV negative women. The cumulative incidence of CIN3+ within the two groups were quite similar to that of CIN2+, suggesting that most women with prevalent CIN2+ also developed CIN3+. Our results suggests that detection of LR-HPV types does not predict CIN3+ and therefore should be omitted from primary screening for cervical cancer.